Validation of a noninvasive aMMP‐8 point‐of‐care diagnostic methodology in COVID‐19 patients with periodontal disease. Issue 4 (11th July 2022) - Gupta, Shipra; Mohindra, Ritin; Singla, Mohita; Khera, Sagar; Kumar, Amit; Rathnayake, Nilminie; Sorsa, Timo; Pfützner, Andreas; Räisänen, Ismo T.; Soni, Roop K.; Kanta, Poonam; Jain, Akanksha; et al.
Abstract: Objectives: The aim of this study was to validate an active matrix metalloproteinase (MMP‐8) point‐of‐care diagnostic tool in COVID‐19 patients with periodontal disease. Subjects, Materials, and Methods: Seventy‐two COVID‐19‐positive and 30 COVID‐19‐negative subjects were enrolled in the study. Demographic data were recorded, periodontal examination carried out, and chairside tests run for evaluating the expression of active MMP‐8 (aMMP‐8) in the site with maximum periodontal breakdown via gingival crevicular fluid sampling as well as via a mouth rinse‐based kit for general disease activity. In COVID‐19‐positive patients, the kits were run again once the patients turned COVID‐19 negative. Results: The overall ( n = 102) sensitivity/specificity of the mouthrinse‐based kits to detect periodontal disease was 79.41%/36.76% and that of site‐specific kits was 64.71%/55.88% while adjusting for age, gender, and smoking status increased the sensitivity and specificity (82.35%/76.47% and 73.53%/88.24, respectively). Receiver operating characteristic (ROC) analysis for the adjusted model revealed very good area under the ROC curve 0.746–0.869 ( p < .001) and 0.740–0.872 ( p < .001) (the aMMP‐8 mouth rinse and site‐specific kits, respectively). No statistically significant difference was observed in the distribution of results of aMMP‐8 mouth rinse test ( p = .302) and aMMP‐8 site‐specific test ( p = .189) once the subjects recovered from COVID‐19. Conclusions: The findings of the present study support the aMMP‐8 point‐of‐care testing (PoCT) kits as screening tools for periodontitis in COVID‐19 patients. The overall screening accuracy can be further increased by utilizing adjunctively risk factors of periodontitis. The reported noninvasive, user‐friendly, and objective PoCT diagnostic methodology may provide a way of stratifying risk groups, deciding upon referrals, and in the institution of diligent oral hygiene regimens.